IS IT DESIRABLE TO TAKE A WORLD BANK LOAN FOR STRENGTHENING LOCAL GOVERNMENTS IN KERALA? - V. Santhakumar and Pinaki Chakraborty (Centre for Development Studies, 2008)
This note analyses the desirability of a loan from the World Bank for strengthening local governments of Kerala under two scenarios. First, is the case where the loan supplements the resources of the local governments in addition to the funds they are entitled to from the state government in the eleventh plan. In this scenario, the spending ability and effectiveness of the local governments are the important issues ofconcern. The paper identifies certain areas where additional resources may be required for the local governments. The second case is where the state government directly or indirectly substitutes a part of the resource that it has committed to give to the local governments, with the proposed loan. In this scenario, the cost of borrowing of the state government is the prime concern, and in this context there are significant advantages intaking a loan from the Bank. The paper also considers a similar loan provided by the Bank to the state of Karnataka to strengthen its local governments and the conditions it came with, and deliberates on the appropriateness of such conditions in the context of Kerala